2002
DOI: 10.1159/000063052
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of the genomic organization of rat chromosome 10

Abstract: Using FISH and RH mapping a chromosomal map of rat chromosome 10 (RNO10) was constructed. Our mapping data were complemented by other published data and the final map was compared to maps of mouse and human chromosomes. RNO10 contained segments homologous to mouse chromosomes (MMU) 11, 16 and 17, with evolutionary breakpoints between the three segments situated in the proximal part of RNO10. Near one of these breakpoints (between MMU17 and 11) we found evidence for an inversion ancestral to the mouse that was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…From approximately the band 10q23 to its telomere, RNO10 corresponds to the entire HSA17, representing the longest region of conserved synteny between humans and rodents. 33 However, based on the comparison of the rat and the human draft DNA sequence, it is clear that the conservation with respect to gene order is not so great and that several intrachromosomal rearrangements have taken place in this region during the divergence between human and rat (Table VI). Starting from HSA17p telomere (PRH3AL, 0.06 Mb) till position of TP53 in the human DNA sequence (7.51 Mb), it is necessary to subdivide HSA17 into at least five segments (Table VI, segments A-E), which have been involved in different intrachromosomal rearrangements to generate the present RNO10 configuration.…”
Section: Ai In 12 Tumorsmentioning
confidence: 99%
“…From approximately the band 10q23 to its telomere, RNO10 corresponds to the entire HSA17, representing the longest region of conserved synteny between humans and rodents. 33 However, based on the comparison of the rat and the human draft DNA sequence, it is clear that the conservation with respect to gene order is not so great and that several intrachromosomal rearrangements have taken place in this region during the divergence between human and rat (Table VI). Starting from HSA17p telomere (PRH3AL, 0.06 Mb) till position of TP53 in the human DNA sequence (7.51 Mb), it is necessary to subdivide HSA17 into at least five segments (Table VI, segments A-E), which have been involved in different intrachromosomal rearrangements to generate the present RNO10 configuration.…”
Section: Ai In 12 Tumorsmentioning
confidence: 99%
“…Recent analysis showed that chromosome 10 of the rat differs by several chromosome rearrangements from both the mouse and the human homologs [27], see also [28]. Here we report on the evaluation of the insertion/deletion pattern in a sample consisting of immune genes (with all intron sequences and with 5000nt of flanking sequence on each side) from human, mouse, and rat.…”
Section: An Applicationmentioning
confidence: 94%
“…Recent analysis showed that chromosome 10 of the rat differs by several chromosome rearrangements from both the mouse and the human homologues, see also ref . It is of interest whether this increased activity is associated with an elevated indel rate in the mouse.…”
Section: An Applicationmentioning
confidence: 99%
“…It is shown that this human chromosome is represented by a single synteny in mouse (MMU11), rat (RNO10), cattle (BTA19), pig (SSC12), horse (ECA11), shrew ( h arm of chromosome hn ), and cat (chromosome E1) (Larkin et al, 2000(Larkin et al, , 2004Behboudi et al, 2002;Chowdhary et al, 2002;Waterston et al, 2002;Menotti-Raymond et al, 2003;Evertsvan der Wind et al, 2004). Zoo-FISH analysis of various mammalian genomes showed single chromosomes painted with HSA17 probe in ten orders of mammals.…”
Section: Introductionmentioning
confidence: 99%